Positive effects of a child‐centered intervention on children's fear and pain during needle procedures. Issue 1 (6th February 2023) - Kleye, Ida; Sundler, Annelie. J.; Karlsson, Katarina; Darcy, Laura; Hedén, Lena
Abstract: To examine whether children experience less fear or pain using a child‐centered intervention and if there were differences between the intervention group and the control group regarding heart rate, time required for the procedure, success rate for the cannula insertion, and patient satisfaction. A controlled single‐center case study of observational design, with one control and one intervention group. Child self‐reported fear or pain levels did not reveal any differences for those receiving the intervention compared with controls. However, according to a behavioral observation measure with the Procedure Behavior Check List, effects of the intervention were lower distress in relation to fear and pain during the cannula insertion. The time it took to perform the cannula insertion also decreased significantly in the intervention group. More children in the intervention group reported that they were satisfied with the needle procedure compared with the children in the control group. The child‐centered intervention provides reduced observed distress related to fear and pain in children undergoing a cannula insertion and reduced total time by more than 50%. This study found that child involvement in care strengthen their ability to manage a needle procedure.